2019
DOI: 10.1021/acssuschemeng.8b06182
|View full text |Cite
|
Sign up to set email alerts
|

Silver–Iron Hierarchical Microflowers for Highly Efficient H2O2 Nonenzymatic Amperometric Detection

Abstract: This study addresses the fabrication of monodispersed iron-doped silver meso-hierarchical flower-like structures via a facile chemical procedure. The morphology of the obtained silver particles has been tuned by changing the concentration of the structure-directing agent (malonic acid). Ball-shaped silver particles were formed in the absence of malonic acid (MA), while silver particles with craspedia-globosa, chrysanthemum, and dahlia flower-like structures were obtained in the presence of 0.2, 0.5, and 1 mM m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Silver nanoparticles have attracted immense attention for many decades because of their diverse applications. The use of silver-based electrochemical sensors for sensing toxicity has attracted considerable interest. The catalytic activity of such systems depends on the particle size, surface morphologies, and crystal orientation. Regarding this, many studies have reported on the use of an electrodeposition method for fabricating Ag-based sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Silver nanoparticles have attracted immense attention for many decades because of their diverse applications. The use of silver-based electrochemical sensors for sensing toxicity has attracted considerable interest. The catalytic activity of such systems depends on the particle size, surface morphologies, and crystal orientation. Regarding this, many studies have reported on the use of an electrodeposition method for fabricating Ag-based sensors.…”
Section: Introductionmentioning
confidence: 99%
“…For example, H 2 O 2 is widely used as a fungicide and preservative in foods like milks to kill bacteria and prevent deterioration. However, an excessive level of H 2 O 2 ingestion and accumulation in human system would cause cytotoxic effects on cells, which may result in some cells related diseases such as disorder of central nervous system, cardiovascular diseases, or even worse of tumors and Alzheimer’s . Therefore, developing a facile, efficient, and reliable biosensor platform for real time H 2 O 2 detection is of significance importance and highly demanded.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen peroxide (H 2 O 2 ), an indispensable chemical, plays significant roles in various industries, such as, textile, papermaking, food manufacturing, and pharmaceuticals. [1][2][3] However, in the food industries, the overuse of H 2 O 2 is detrimental for the health of human-beings due to its toxicity according to GB 2760-86 (hygienic standard of food additives of China). In addition, H 2 O 2 has been identified to be involved in many physiological processes, where the high-level secretion of H 2 O 2 from living organisms always associates with some severe illness, like diabetes, cancer, atherosclerosis, Parkinson's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen peroxide (H 2 O 2 ), an indispensable chemical, plays significant roles in various industries, such as, textile, papermaking, food manufacturing, and pharmaceuticals [1–3] . However, in the food industries, the overuse of H 2 O 2 is detrimental for the health of human‐beings due to its toxicity according to GB 2760‐86 (hygienic standard of food additives of China).…”
Section: Introductionmentioning
confidence: 99%